Visões imperialistas em Moby Dick, de Herman Melville - Satorno, Marla Silva do Vale (2014)
This article briefly analyses how the imperialist images and beliefs about the Other are strongly present in American writer Herman Melille, from his character Ishmael’s impressions about Queequeg, the New-Zeland native and the African Prince Dagoo. Based on authors such as Edward Said, Homi K. Bhabha and others, we intend to present the presence of imperialist beliefs and images in Melville’s text. Yet he is considered an anti-imperialist activist, it is possible to notice its influence on the characters’ images, speech and attitude.